(untitled) (Jurnal Lemhannas RI, 2025)
Purpose: This study aims to analyse the role of automation technologies in strengthening national resilience through the Indonesian Army by integrating the Technology–Organization–Environment (TOE) framework with the Asta Gatra concept. The analysis positions defence automation as a strategic instrument that reinforces the ideological, political, economic, and security dimensions of national resilience in an archipelago. Study Design/Methodology/Approach: This study adopts a qualitative descriptive design using thematic analysis of policy documents, official military publications, academic literature, and expert insights. The analysis examines technological readiness, organisational capacity, and environmental pressures that shape defence transformations in Indonesia. Findings: Defence automation faces challenges in the form of infrastructure gaps, institutional fragmentation, and inequality in human resource development. The geopolitical dynamics of the Indo-Pacific demand adaptive and integrated defence governance, so strengthening national resilience depends on institutional reform, cross-sector coordination, and strategic policy alignment. Originality/Value: This study contributes by embedding defence automation within the Asta Gatra framework and proposing an integrated approach that connects technological innovation with national resilience governance. The framework offers strategic insights for strengthening defence capabilities while maintaining social cohesion, political legitimacy, and sustainable national security.